The Relationship Between Peer Support and Psychological Distress among the Undergraduates in Hebei Province, China: A Concept Paper (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
The health care system relies heavily on peer assistance. Peer support's effects in a university setting, however, have reportedly been deemed inadequate. By analyzing the preview reviews, this study aims to examine how peer support affects psychological discomfort in an academic setting. Peer support, however, does not always have an impact on the psychological discomfort of college students. To undertake more research, the inner potential mechanism between psychological discomfort and peer support must be investigated. The Social Identity hypothesis, which looks at how people define themselves in social groups, is a good hypothesis. It was put forth by psychologists Tajfel and Turner in the 1970s. The Psychology Distress Scale, created by Kessler et al. (2003), and the Peer Support Scale, created by Kuo et al. (2007), were used to create and validate this instrument to have a deeper comprehension of this issue.